2010
DOI: 10.1039/c0ob00136h
|View full text |Cite
|
Sign up to set email alerts
|

The biphenyl-monitored effective size of unsaturated functional or fluorinated ortho substituents

Abstract: The size of a series of typical substituents has been probed by dynamic NMR measurements of the barriers to aryl-aryl rotation of the corresponding biphenyls. The resulting B values are meaningful because only mono-ortho substituted compounds were investigated and thus the results are not compromised by the non-additivity of multiple steric effects. On the basis of the chosen model system ethynyl and cyano groups were found to be slightly smaller than a phenyl ring. In contrast, vinyl and, in particular, formy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 44 publications
1
21
0
1
Order By: Relevance
“…the B value) of the substituted biphenyl. A number of diasterotopic probes in the 3′-position of 2-substituted biphenyls were tested for this purpose: Me 2 CH, 7 (i-Pr) 3 Si, 8 i-PrMe 2 Si, 8,10 (CF 3 ) 2 COH 9 and it was demonstrated that the rotational barrier was found to remain the same, within the experimental uncertainty of ±0.15 kcal mol , regardless of the choice of probe. For instance the barriers determined using the isopropyl group as a probe were found 7 to be 15.4, 8.75 and 9.9 kcal mol −1 for biphenyls bearing, as an ortho substituent, t-Bu, Br and I, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…the B value) of the substituted biphenyl. A number of diasterotopic probes in the 3′-position of 2-substituted biphenyls were tested for this purpose: Me 2 CH, 7 (i-Pr) 3 Si, 8 i-PrMe 2 Si, 8,10 (CF 3 ) 2 COH 9 and it was demonstrated that the rotational barrier was found to remain the same, within the experimental uncertainty of ±0.15 kcal mol , regardless of the choice of probe. For instance the barriers determined using the isopropyl group as a probe were found 7 to be 15.4, 8.75 and 9.9 kcal mol −1 for biphenyls bearing, as an ortho substituent, t-Bu, Br and I, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…8C Time, h 6 7 8 9 10 b 1 H 1 25 3 55 36 4 5 -2 4 25 3 50 42 4 4 -3 4 25 144 8 72 4 16 -4 4 a 80 16 29 51 -20 -5 Me 1 25 16 64 5 13 18 0 6 2 25 16 52 7 13 21 5 7 5 25 144 49 6 9 25 11 8 n Pr 1 25 5 83 3 13 1 0 9 1 25 48 82 2 12 4 0 10 5 25 144 42 6 22 24 6 11 1 40 5 44 10 8 23 9 neither trifluoroester from 8 nor pentafluoro diethers from 9 were formed by OH/F permutation, even in the presence of a large excess of DAST or at longer reaction times. This means that, although the ethoxydifluoromethyl group is less electron-withdrawing than the ethoxycarbonyl group, it is bulky enough [31,32] to divert the attack exclusively at the second carbonyl group.…”
Section: Entry R Conditionsmentioning
confidence: 97%
“…Here, both steric and electronic effects play a synergic role in promoting the carbonyl fluorination. Though CF 3 group exerts an inductive electron-withdrawing effect comparable, if not slightly lower, to that of -CO 2 Et group, its steric requirements are substantially larger [32] and the attack of DAST to OH group becomes all the more difficult.…”
Section: Entry R Conditionsmentioning
confidence: 98%
See 1 more Smart Citation
“…[31] Up to now, such "B values" have been determined for more than two dozen substituents. [31][32][33] The measurements were accomplished by variable-temperature ("dynamic") NMR spectroscopy, monitoring the flip of the axially chiral biphenyl conformer into its mirror image by means of diastereotopicity probes such as an isopropyl, [34] isopropyldimethylsilyl, [31] or hexafluoro-α-hydroxyisopropyl [32] group located at the 3Ј-position. [35] …”
Section: Introductionmentioning
confidence: 99%